The Paradox of the Pouch: A Systematic-Narrative Hybrid Review of Snus and Nicotine Pouch Use on Athletic Performance, Prevalence, Health Outcomes, and Regulatory Status in Sport - Alansi, Abdulrahman; Weng, Kai-chiun; Kravets, Alesia; Zhukava, Lizaveta; Chrobak, Agata; Bessmylna, Kateryna; Volkava, Darya; Sakovich, Volha; Kacynel, Ewa; Myślicka, Wiktoria (Quality in Sport, 2026)
Background. Oral nicotine products, including traditional snus and tobacco-free nicotine pouches (ONPs), are increasingly common among elite athletes [11, 15, 21]. They bypass the respiratory route via sublabial administration and are rapid and concentrated [5, 20]. Athletes use them as cognitive enhancers and stress and appetite suppressors [18, 30]. Nevertheless, a paradox remains: athletes consume ONPs seeking an ergogenic advantage despite no evidence and substantial health risks [17, 31]. Aim. This review combines current knowledge on the prevalence of ONPs in sports, critically reviews their effects on physical and cognitive performance, and examines associated health, toxicological, and regulatory implications. Materials and methods. Relevant literature from sports science, toxicology, and public health was reviewed, focusing on health and regulatory impacts of oral nicotine in athletic and general populations [6, 27]. The search used Google Scholar, PubMed, and other databases to evaluate recent developments comprehensively. Results. Evidence shows nicotine does not enhance physical performance and may impair cardiovascular readiness, anaerobic capacity, and physical endurance [18, 30, 31]. Perceived cognitive improvements stem from relief of nicotine withdrawal symptoms [17, 30]. Furthermore, ONPs risk oral damage, systemic cardiac strain, and addiction [4, 9, 24]. The unclear regulatory status of nicotine in sports, with aggressive marketing that exploits "tobacco-free" legal loopholes, demand updated anti-doping policies [8, 16, 25]. Conclusion. ONPs may serve as a harm-reduction tool for adult smokers [1, 19, 23], spread among nicotine-naïve athletes poses a novel and growing public health threat [7, 27]. Educational interventions, along with more extensive screening by sports governing bodies, are essential for athletes welfare.